2011
DOI: 10.1021/ja2007643
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Methods for Synthesis of Internal (α-) Vinylboronates through Efficient NHC–Cu-Catalyzed Hydroboration of Terminal Alkynes. Utility in Chemical Synthesis and Mechanistic Basis for Selectivity

Abstract: Cu-catalyzed methods for site-selective hydroboration of terminal alkynes, where the internal or α-vinylboronate is generated predominantly (up to >98%) are presented. Reactions are catalyzed by 1-5 mol % of N-heterocyclic carbene (NHC) complexes of copper, easily prepared from N-aryl-substituted commercially available imidazolinium salts, and proceed in the presence of commercially available bis(pinacolato)diboron [B(2)(pin)(2)] and 1.1 equiv of MeOH at -50 to -15 °C in 3-24 h. Propargyl alcohol and amine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
158
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(184 citation statements)
references
References 85 publications
3
158
0
2
Order By: Relevance
“…These potent reagents find many applications, such as in the Suzuki-Miyaura cross-coupling reaction. In 2011, Hoveyda and co-workers published a highly efficient and selective process for the hydroboration of terminal alkynes [67,68]. The N-substituents of NHC ligands allowed to control the selectivity.…”
Section: Boration Of Alkynesmentioning
confidence: 99%
“…These potent reagents find many applications, such as in the Suzuki-Miyaura cross-coupling reaction. In 2011, Hoveyda and co-workers published a highly efficient and selective process for the hydroboration of terminal alkynes [67,68]. The N-substituents of NHC ligands allowed to control the selectivity.…”
Section: Boration Of Alkynesmentioning
confidence: 99%
“…[17] Remarkably, inversions of regioselectivities have been observed, particularly by introducing different copper ligands. [18][19][20][21][22][23] For aryl-substituted terminal alkynes, and with nonbulky ligands, the selectivity is generally in favor of the linear adduct (or -product, Scheme 1).…”
mentioning
confidence: 99%
“…Noteworthy, after a round of optimization, [26] we found that the different experimental conditions to get Linear (RT) or Branched (-20°C) derivatives described by Hoveyda were also the most efficient in our case. [18] We then operated a review of various electronic effects on the alkyne aryl group in all ortho, meta and para positions. (α-ICyD)CuCl consistently gave the linear product whereas (-ICyD)CuCl gave the branched compound as the major one.…”
mentioning
confidence: 99%
See 2 more Smart Citations